The Prevalence and Correlates of Social Anxiety Symptoms among People with Schizophrenia in Ethiopia: An Institution-Based Cross-Sectional Study. (25th March 2020) - Kibru, Boki; Tesfaw, Getachew; Demilew, Demeke; Salelew, Endalamaw
Abstract : Background . The comorbidity of social anxiety disorder is very common in schizophrenia patients and affects almost all age groups. This social anxiety disorder negatively impacts the quality of life, medication adherence, and treatment outcomes of people with schizophrenia. It is not well recognized in clinical settings. Therefore, assessing social anxiety symptoms and its associated factors was significant to early intervention and management of schizophrenia patients in Ethiopia. Methods . An institution-based cross-sectional study was conducted at Amanuel Mental Specialized Hospital in Addis Ababa, Ethiopia. Data collectors randomly recruited 423 schizophrenic patients by using the systematic sampling technique. A face-to-face interviewer-administered questionnaire was used to collect data. The standardized Liebowitz Social Anxiety Scale (LSAS) was employed to assess individual social anxiety symptoms. We computed bivariate and multivariate binary logistic regressions to identify factors associated with social anxiety symptoms. Statistical significance was declared at p < 0.05 . Results . The prevalence of social anxiety symptoms was 36.2% (95% CI: 31.50, 40.80). Male sex (AOR = 2.03, 95% CI: 1.20, 3.44), age of onset of schizophrenia (AOR = 1.91, 95% CI:1.17, 3.12), positive symptoms (AOR = 0.75, 95% CI:0.67, 0.83), depression/anxiety symptoms (AOR = 1.29, 95% CI: 1.18, 1.41), number of hospitalizations (AOR = 2.80, 95% CI:1.32, 5.80), and suicidal ideation (AOR = 0.44, 95% CI: 0.26, 0.74) were factors significantly associated with social anxiety symptoms at p < 0.001, whereas poor social support (AOR = 5.23, 95% CI:2.03, 14.70) and suicide attempts (AOR = 1.93, 95% CI: 1.14, 3.26) were statistically associated with social anxiety symptoms at p < 0.01 . Conclusion . The prevalence of social anxiety symptoms among schizophrenia patients was found to be high. Timely treatment of positive and depression/anxiety symptoms and suicide risk assessments and interventions need to be done to manage the problems.